The relative importance of visual and olfactory cues to onion thrips (Thrips tabaci) in host and nonhost crops - Skill, S.M.; Davidson, M.M.; Butler, R.C. (New Zealand Plant Protection, 2012)
Onion thrips are a key pest in onion crops on a global scale and are known to respond to visual (eg coloured traps) and olfactory (eg ethyl isonicotinate (Ei)) cues In order to better understand how such cues could be exploited to help manage this pest an experiment was set up in an onion and an adjacent wheat crop to compare the relative importance of olfactory and visual cues in a host and nonhost crop Blue (visual cue) and green (nonvisual cue) sticky traps were placed on poles at canopy height in both crops both with and without an Ei lure (olfactory cue) in spring (2011) for 7 days Approximately eight times more onion thrips were caught in the wheat field (P0031) than in the onion crop where very few were caught (151 total onion thrips) The olfactory cue was stronger than the visual cue in both crops With the Ei lure green traps caught around 27 (onion) or 330 (wheat) thrips and blue traps caught around 30 (onion) or 35 (wheat) thrips on average Without the lure green traps caught less than 1 for both crops while blue traps caught around 05 (onion) or 59 (wheat) thrips